Dental caries and body mass index in Mosul City schoolchildren - Yaseen, Hadeel Abdullah; Gasgoos, Saher Sami (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: There is a potential correlation between tooth loss and dental caries in both obese and underweight patients. The presence of extensive dental caries can delay the process of eating, leading to a subsequent decrease in body weight. Purpose: The objective of this study was to examine the correlation between dental caries and body mass index (BMI) in schoolchildren residing in Mosul City. Methods: The present cross-sectional study was conducted on a randomized sample of 7- to 10-year-old school students. The study assessed the clinical characteristics, namely the decayed, missing, and filled teeth (DMFT/dmft) index. The DMFT index represents the number of decayed, missing, and filled teeth in the permanent dentition, while the dmft index pertains to deciduous dentition. After adjusting for age, gender, height, and weight, BMI-age percentiles were determined using the BMI Percentile Calculator for Children and Teens. Children were then categorized as underweight, normal weight, overweight, or obese. In the statistical analysis, the Kruskal–Wallis test was employed to examine variations between categorical variables. Results: The prevalence of dental caries in primary dentition was found to be 80.33%, whereas in permanent dentition, it was 50.33%. The majority of children affected by caries were in the obesity and overweight categories, followed by those with normal weight, while the lowest proportion was observed among underweight children. Conclusion: The findings indicate variations in the occurrence of dental caries across different subgroups of children based on their BMI-age percentiles.